2019
DOI: 10.1080/08998280.2019.1646598
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolar hyperglycemic syndrome in a young boy

Abstract: We describe a 6-year-old boy who presented to the emergency department with the complaint of nausea and vomiting with diarrhea. Workup revealed a glucose level of 1904 mg/dL, and hyperglycemic hyperosmolar syndrome was diagnosed. Hyperglycemic hyperosmolar syndrome is very rare in the pediatric population, but recent published reports suggest that the incidence of this disorder may be increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is rare among children, but most cases are associated with new-onset type 1 diabetes or uncontrolled type 2 diabetes mellitus. Recently, more cases have been reported with an increase in the frequency of type 2 diabetes ( 1 , 2 , 3 ). Reports have indicated that the risk factors for HHS include complications of pneumonia and urinary tract infections, cerebrovascular accidents, drugs, peritoneal dialysis, burns, and dehydration ( 1 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is rare among children, but most cases are associated with new-onset type 1 diabetes or uncontrolled type 2 diabetes mellitus. Recently, more cases have been reported with an increase in the frequency of type 2 diabetes ( 1 , 2 , 3 ). Reports have indicated that the risk factors for HHS include complications of pneumonia and urinary tract infections, cerebrovascular accidents, drugs, peritoneal dialysis, burns, and dehydration ( 1 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more cases have been reported with an increase in the frequency of type 2 diabetes ( 1 , 2 , 3 ). Reports have indicated that the risk factors for HHS include complications of pneumonia and urinary tract infections, cerebrovascular accidents, drugs, peritoneal dialysis, burns, and dehydration ( 1 , 3 ). HHS is also caused by severe hyperglycemia due to the administration of glucocorticoids, excessive diuretics, and atypical antipsychotics ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations